Answer:
About 34
Step-by-step explanation:
There are 168 chocolate chips in 5 ounces. That means you want to know how many chips there are per ounce. Divide 168 by 5 and you get approximately 34 chocolate chips per ounce (33.6 if you need this)
Answer:
34
Step-by-step explanation:
All you have to do is divide
168 / 5 = 33.6
so about 34 chocolate chips in an ounce
The length of a rectangle is 9 cm more than its
width. If the area of the rectangle is 36 cm2,
what are the dimensions? Justify your answer.
= 4 = x²
x = Answer: Length= 11 , Brteadth = 2
Step-by-step explanation: Let the breadth of the rectangle be x
length = 9 + x
area = 36 cm²
A.T.Q
36cm² = 9x*x
36 = 9x²
36/9 = 4 = x²
x = root of 4
x= 2
Therefore , breadth of rectangle is 3cm and length is 12 cm
verification:
l*b = 12*3 = 36cm²
write the following quadratic equation to standard form and find a,b,c
1) 2x²=3x
2)4x²-10=5
3)3(x²-4x)=2(x+2)
4)3x(x+2x)=11
5)6x(x-8)=2x²+4
1) The standard form of the equation is 2x² - 3x = 0, a = 2 , b = -3 ,
c = 0
2) The standard form of the equation is 4x² - 15 = 0, a = 4 , b = 0 ,
c = -15
3) The standard form of the equation is 3x² - 14x - 4 = 0, a = 3 , b = -14 ,
c = -4
4) The standard form of the equation is 9x² - 11 = 0, a = 9 , b = 0 ,
c = -11
5) The standard form of the equation is 4x² - 48x - 4 = 0, a = 4 , b = -48 ,
c = -4
Step-by-step explanation:
The standard form of a quadratic equation is ax² + bx + c = 0, where
a is the coefficient of x²b is the coefficient of xc is the numerical term1)
∵ 2x² = 3x
- Subtract 3x from both sides
∴ 2x² - 3x = 0
∵ The coefficient of x² = 2
∴ a = 2
∵ The coefficient of x = -3
∴ b = -3
∵ There is no numerical term
∴ c = 0
The standard form of the equation is 2x² - 3x = 0, a = 2 , b = -3 , c = 0
2)
∵ 4x² - 10 = 5
- Subtract 5 from both sides
∴ 4x² - 10 - 5 = 0
- Add like terms
∴ 4x² - 15 = 0
∵ The coefficient of x² = 4
∴ a = 4
∵ There is no x term
∴ b = 0
∵ The numerical term = -15
∴ c = -15
The standard form of the equation is 4x² - 15 = 0, a = 4 , b = 0 , c = -15
3)
∵ 3(x² - 4x) = 2(x + 2)
- Simplify each side
∴ 3x² - 12x = 2x + 4
- Subtract 2x from both sides
∴ 3x² - 12x - 2x = 4
- Subtract 4 from both sides
∴ 3x² - 12x - 2x - 4 = 0
- Add like terms
∴ 3x² - 14x - 4 = 0
∵ The coefficient of x² = 3
∴ a = 3
∵ The coefficient of x = -14
∴ b = -14
∵ The numerical term = -4
∴ c = -4
The standard form of the equation is 3x² - 14x - 4 = 0, a = 3 , b = -14 ,
c = -4
4)
∵ 3x(x + 2x) = 11
- Add the terms in the bracket
∴ 3x(3x) = 11
- Simplify the left hand side
∴ 9x² = 11
- Subtract 11 from both sides
∴ 9x² - 11 = 0
∵ The coefficient of x² = 9
∴ a = 9
∵ There is no x term
∴ b = 0
∵ The numerical term = -11
∴ c = -11
The standard form of the equation is 9x² - 11 = 0, a = 9 , b = 0 ,
c = -11
5)
∵ 6x(x - 8) = 2x² + 4
- Simplify the left hand side
∴ 6x² - 48x = 2x² + 4
- Subtract 2x² from both sides
∴ 4x² - 48x = 4
- Subtract 4 from both sides
∴ 4x² - 48x - 4 = 0
∵ The coefficient of x² = 4
∴ a = 4
∵ The coefficient of x = -48
∴ b = -48
∵ The numerical term = -4
∴ c = -4
The standard form of the equation is 4x² - 48x - 4 = 0, a = 4 , b = -48 ,
c = -4
Learn more:
You can learn more about quadratic equations in brainly.com/question/9390381
#Learnwith Brainly
Noreen is considering a purchase of a $170,000 home and her bank is
offering her a 5.15% interest rate on a 30-year mortgage with an option of
purchasing points. The bank is requiring a 20% down payment. If she decides
to apply the price of 2 points to her down payment instead, what will her
monthly mortgage payment be? Round your answer to the nearest dollar.
Answer:$728
Step-by-step explanation:
Final answer:
To provide Noreen with her new monthly mortgage payment, the cost of 2 mortgage points is added to the original 20% down payment, resulting in a decreased loan amount. A mortgage calculator or formula is then used to determine the monthly payment at a 5.15% interest rate for the new loan amount over 30 years, which would be higher than with the points purchased. Answer : 725$
Explanation:
To calculate Noreen's monthly mortgage payment, we need to first understand the impact of her decision to apply the price of 2 points to her down payment instead of purchasing points. Points are upfront fees paid to the lender at closing in exchange for a reduced interest rate. One point is equal to 1% of the loan amount. However, since Noreen is opting to add the cost of these points to her down payment, we'll calculate her down payment and loan amount without considering a reduction in interest rate.
1. Calculate the down payment:
Noreen's home costs $170,000, and she is required to make a 20% down payment.
Down payment = 20% of $170,000 = 0.20 * $170,000 = $34,000
2. Calculate the cost of 2 points:
Since Noreen is not buying points and instead adding this cost to her down payment, we calculate the initial loan amount to find out how much 2 points would cost.
Initial loan amount without points = $170,000 - $34,000 = $136,000
Cost of 2 points = 2% of $136,000 = 0.02 * $136,000 = $2,720
3. Adjust the down payment:
Noreen decides to add the $2,720 (cost of 2 points) to her down payment.
New down payment = $34,000 + $2,720 = $36,720
4. Calculate the new loan amount:
New loan amount = Home price - New down payment = $170,000 - $36,720 = $133,280
Now, we use the loan amount of $133,280 and the original interest rate of 5.15% to calculate the monthly mortgage payment over a 30-year term.
The formula for monthly mortgage payments is:
[tex]\[M = P\frac{r(1+r)^n}{(1+r)^n - 1}\][/tex]
First, calculate the monthly interest rate:
[tex]\[r = \frac{0.0515}{12} = 0.00429167\][/tex]
Then, plug in the values into the formula:
[tex]\[M = 133,280\frac{0.00429167(1+0.00429167)^{360}}{(1+0.00429167)^{360} - 1}\][/tex]
This calculation can be complex, so it's often easiest to use a mortgage calculator or financial calculator to compute \(M\).
When you perform this calculation, you should get:
[tex]\[M \approx 725\][/tex]
Thus, Noreen's monthly mortgage payment would be approximately $725 when rounded to the nearest dollar. Please note, the exact payment can slightly vary based on the precision of the interest rate conversion and the calculation method.
how do I solve for w
Answer:
w ≥ 141/2
Step-by-step explanation:
12 − 4/6 w ≤ 2/8 − 3/6 w
First, combine like terms. Add 4/6 w to both sides, and subtract 2/8 from both sides.
12 − 2/8 ≤ 4/6 w − 3/6 w
12 − 2/8 ≤ 1/6 w
Reduce 2/8 to 1/4:
12 − 1/4 ≤ 1/6 w
To get rid of the fractions, multiply both sides by 12 (the LCM of 4 and 6):
12 (12 − 1/4) ≤ 12 (1/6 w)
144 − 3 ≤ 2w
141 ≤ 2w
Divide by 2:
141/2 ≤ w
If you'd like, flip the equation:
w ≥ 141/2
Factor each expression 12x + 24
Answer:
12(x+2)
Step-by-step explanation:
Factor a 12 out of
12x + 24
12 goes into 12 once
12 goes into 24 twice
= 12(x+2)
write an equation in slope for a line that passes through (3,4) (and has a y intercept of -8)
Answer:
Part 1) The equation in slope intercept form is [tex]y=4x-8[/tex]
Step-by-step explanation:
Part 1) Write an equation in slope-intercept form for a line that passes through (3,4) (and has a y intercept of -8)
we know that
The equation of a line in slope intercept form is equal to
[tex]y=mx+b[/tex]
where
m is the slope
b is the y-intercept
we have
[tex]b=-8[/tex]
[tex]point\ (3,4)[/tex]
substitute
[tex]4=m(3)-8[/tex]
solve for m
[tex]4+8=3m[/tex]
[tex]3m=12[/tex]
[tex]m=4[/tex]
therefore
[tex]y=4x-8[/tex]
The sum of two numbers, x and y, is 142. Their
could be used to find the numbers?
nbers,
and y, is 142. Their difference is 14. Which system of equations
x + 142 = y
+
18.64
x + y = 142
y = 14
B.
- 14 = y
c
x - y = 142
x + y = 14
D.
14
x=142 + y
y = 14- X
+
The system that will be used to find the numbers
x+y=142
x-y = 14
Step-by-step explanation:
The linear equations are used for representing real life situations
Let x be the first number
and
y be the second number
Then
According to given statement,
"The sum of two numbers, x and y, is 142."
[tex]x+y=142[/tex]
And
"Their difference is 14."
[tex]x-y=14[/tex]
Hence
The system that will be used to find the numbers
x+y=142
x-y = 14
Keywords: Linear Equations
Learn more about linear equations at:
brainly.com/question/2116906brainly.com/question/2131336#LearnwithBrainly
Please answer this correctly
28 to nine means it is 8:32 ( to get this you subtract 28 from 9.) ( its saying there are 28 minutes left until it is 9)
add 8 hours
= 8+ 8 = 16
well we arent talking about military time sooo 16-12 = 4
4 : 32 and you need to add the 59 so
32+ 59 = 91
91 - 60 = 31 (dont forget to add the extra 1 hour because we subtracted 60 minutes :). )
so the correct time will be 5: 31
Answer: 5:31
Step-by-step explanation:
28 minutes to 9 is 8:32
8 hours and 59 minutes later it would be 5:31
Score: 0 of 1 pt
3 of 21 (14 complete)
6.5.25
A family paid $25,900 as a down payment for a home. If this represents 14% of the price of the home, find the price of the home.
The price of the home is $
the answer box and then click Check Answer
The price of house is $185000.
Step-by-step explanation:
The percentage formula will be used for finding the price of the house
Given
Down payment = $25900
Percentage = 14%
Let x be the price of the home
Then
[tex]Down\ payment=14\%\ of\ x\\\\25900=0.14 * x\\\\x = \frac{25900}{0.14}\\\\x =185000[/tex]
Hence,
The price of house is $185000.
Keywords: Down payment, percentage
Learn more about percentage at:
brainly.com/question/10666510brainly.com/question/10699220#LearnwithBrainly
HELP ASAP!!! 100 POINTS!!!
1. It takes the earth 24 h to complete a full rotation. It takes Mercury approximately 58 days, 15 h, and 30 min to complete a full rotation. How many hours does it take Mercury to complete a full rotation? Show your work using the correct conversion factors.
Answer:
HERE IS THE ANSWER 1407.5 hours
Step-by-step explanation:
if 3 miles is equal to 4828.05 miles, how many meters are in 5 miles
There are 8046.75 meters in 5 miles
Step-by-step explanation:
Method 1:
First of all we have to calculate the unit conversion.
Assuming that 3 miles is equal to 4828.05 meters
We have to find that how many meters make one mile
So,
3 miles = 4828.05 meters
[tex]1\ mile=\frac{4828.05}{3}\\=1609.35\ meters[/tex]
Now we know that:
[tex]1\ mile=1609.35\ meters\\5\ miles=1609.35*5 = 8046.74\ meters[/tex]
Method 2:
We can also use ratios to find the number of meters in 5 miles as:
3:4828.05::5:x
where x is the number of meters in 5 miles
[tex]\frac{3}{4828.05}=\frac{5}{x}\\x=\fac{5*4828.05}{3}\\=8046.75\ meters[/tex]
Hence,
There are 8046.75 meters in 5 miles
Keywords: Conversions, Units
Learn more about conversions at:
brainly.com/question/10699220brainly.com/question/10703930#LearnwithBrainly
Solve: In 2x + In 2 = 0
DONE
Answer:
[tex]x=\frac{1}{4}[/tex]
Step-by-step explanation:
We can use some logarithmic rules to solve this easily.
Note: Ln means [tex]Log_e[/tex]
Now, lets start with the equation:
[tex]ln(2x) + ln(2) = 0\\ln(2x) = -ln(2)[/tex]
Writing left side with logarithmic base e, we have:
[tex]Log_{e}(2x) = -ln(2)[/tex]
We can now use the property shown below to make this into exponential form:
[tex]Log_{a}b=x\\means\\a^x=b[/tex]
So, we write:
[tex]Log_{e}(2x) = -ln(2)\\e^{-ln(2)}=2x[/tex]
We recognize another property of exponentials:
[tex]a^{bc}=(a^{b})^{c}[/tex]
So, we write:
[tex]e^{-ln(2)}=2x\\(e^{ln(2)})^{-1}=2x[/tex]
Also, another property of natural logarithms is:
[tex]e^{(ln(a))}=a[/tex]
Now, we simplify:
[tex](e^{ln(2)})^{-1}=2x\\(2)^{-1}=2x\\\frac{1}{2}=2x\\x=\frac{\frac{1}{2}}{2}\\x=\frac{1}{4}[/tex]
This is the answer.
The supermarket has pie filling
on sale for $1.19. Mom bought
four cans. If she gave the clerk
$ 10, what is her change?
Answer:
$5.24
Step-by-step explanation:
If Mom bought 4, she bought [tex]$1.19*4=$4.76[/tex] worth of pie filling. Since she paid $10, she needs [tex]$10-$4.76=$5.24[/tex] change
What is 3 ÷ 2/5? The quotient is 7 and _____
HELP PLEASE
Answer:
Your answer is 15/2 i hoped i helped
Step-by-step explanation:
Answer:
1
Step-by-step explanation:
3×5/2
15/2
The remainder is 1
Please help! :) Need answer fast!
Answer:
x = 3
y = 2
Step-by-step explanation:
When 2 triangles are congruent, they will have exact same 3 sides length and exact same 3 angles measure.
So we can say:
-2x + 6y = 6
and
-7x + 8y = -5
Let's multiply first equation by 7 and 2nd equation by -2, to get:
7 [-2x + 6y = 6] = -14x +42y = 42
and
-2 [-7x + 8y = -5] = 14x - 16y = 10
Now adding these 2 new equations and solving for y:
-14x +42y = 42
14x - 16y = 10
----------------------
26y = 52
y = 52/26
y = 2
Now we put y = 2 into 1st equation (or any other) and solve for x:
-2x + 6y = 6
-2x + 6(2) = 6
-2x + 12 = 6
6 = 2x
x = 6/2
x = 3
What is s=(n - 2)180
Answer:
angle sum of a triangle’Formula
Step-by-step explanation:
N stands for the number of edges, - 2 is the result after finishing, 2 has no special significance. Because the sum of outer angles is a constant n-edge shape with 360 degrees, take n flat angles 180n = inner angle and + 360, so the sum of inner angles = 180n-360 = 180 (n-2)
That formula tells you what is the sum of the interior angles of a polygon with n sides.
So, for example, a triangle has n=3 sides, and in fact the sum of its interior angles is
[tex](3-2)\cdot 180=180[/tex]
As another example, the sum of the interior angles of a polygon with 15 sides is
[tex](15-2)\cdot 180=13\cdot 180=2340[/tex]
megan has a rope that is 15 feet in length she cuts the rope into 4 pieces how long is each section of to
Answer:
3.75
Step-by-step explanation:
You take your 15 feed and divide it by 4 for the four pieces she cuts the rope into giving you with each section of the cut rope being 3.75 in.
The length of each piece is 3.75 feet long.
What is Equation Modelling?Equation modelling is the process of writing a mathematical verbal expression in the form of a mathematical expression for correct analysis, observations and results of the given problem.
We have Megan who has a rope that is 15 feet in length and she cuts the rope into 4 pieces.
Assume that the length of each piece is x ft. Then -
4x = 15
x = 15/4
x = 3.75 ft
Therefore, the length of each piece is 3.75 feet long.
To solve more questions on equation modelling, visit the link below-
brainly.com/question/6593383
#SPJ5
13m-7-10m=2? I need help
Answer:
[tex]\displaystyle 3 = m[/tex]
Step-by-step explanation:
2 = −7 + 3m
+ 7 + 7
__________
[tex]\displaystyle \frac{9}{3} = \frac{3m}{3} \\ \\ 3 = m[/tex]
I am joyous to assist you anytime.
passes through (-5,9) and (1,3)
Answer:
m=-1
Step-by-step explanation:
m=(y2-y1)/(x2-x1)
m=(3-9)/(1-(-5))
m=-6/(1+5)
m=-6/6
m=-1
complete the linear equation
Answer:
[tex]y=-30x[/tex]
Step-by-step explanation:
The intercept of the function is the value of y when x=0. In this particular case, when x=0, y=0, then the intercept is y=0.The slope of the function must tell us what is the change in y when x changes. When x changes in one unit (from x=0 to x=1), y takes the value of y=-30, y=1x(-30). When x takes the value of x=2, y takes the value of y=-60, then y=2x(-30), and when x=3, y=3x(-30)=-90.This means that y always takes the value of -30x. Then the slope is -30, which is the rate of change of y as x changes.For the following exercises, use the function f represented in table 14 below
Evaluate f(3)
Solve f(x)=1
Without Table 14, a specific answer can't be provided. But generally you would find the y value when x is 3 for f(3), or find the x value when y is 1 for f(x)=1.
Explanation:This question pertains to the evaluation of f(3) and solving for f(x)=1 within the given function f that's represented in Table 14. Unfortunately, as the Table 14 isn't provided, I can't give a specific answer. However, generally, to evaluate f(3), find the pair where the x value is 3; the corresponding y (or f(x)) value is the result of f(3). To solve f(x)=1, look for the pair in the table where the f(x) (or y) value is 1; the corresponding x value is the solution for f(x)=1.
Learn more about Function Evaluation here:https://brainly.com/question/12056604
#SPJ2
Write an equation in point slope form (12,7) m=-2
Answer:
y= -2x+31
Step-by-step explanation:
Y=-2x+B
7=-2(12)+B
7=-24+B
7+24= (-24+24)+B
31=B
Y=-2x+31
Hope it helps!!
Simplify x² + 3x + 2/X +1
To simplify the expression x² + 3x + 2 / X + 1, factor the numerator and denominator expressions separately. The simplified form of the expression is (x + 2) / 1.
Explanation:To simplify the expression, x² + 3x + 2 / X + 1, we can use the factoring method. First, we factor the numerator expression. The expression x² + 3x + 2 can be factored as (x + 2)(x + 1). Then, we factor the denominator expression X + 1. So, the simplified form of the expression is (x + 2) / 1.
Learn more about expressionhttps://brainly.com/question/723406
#SPJ11
At present Asha's age (in years) is two more than the square of her daughter Nisha's age (in years). When Nisha grows to her mother's present age, Asha's age would be one year less than 10 times the present age of Nisha. Find the present age of Asha and Nisha
Answer:
Asha's present age is 27 years and Nisha's present age is 5 years.
Step-by-step explanation:
Let the present age of Nisha be [tex]x[/tex] years.
As per question, Asha's present age is 2 more than the square of Nisha's age.
[tex]\therefore[/tex] Asha's present age = [tex]x^2+2[/tex]
Now, Nisha will reach her mother's age after [tex]x^2+2-x[/tex] years.
Therefore, age of Asha after [tex]x^2+2-x[/tex] years will be = [tex]x^2+2+x^2+2-x=2x^2-x+4[/tex]
Now, as per question,
[tex]2x^2-x+4=10x-1\\2x^2-x-10x+4+1=0\\2x^2-11x+5=0\\2x^2-x-10x+5=0\\x(2x-1)-5(2x-1)=0\\(2x-1)(x-5)=0\\x=\frac{1}{2}\ or\ x=5[/tex]
As age can't be in fraction, we consider the present age of Nisha as 5 years. So, Asha's present age is [tex]x^2+2=5^2+2=25+2=27[/tex] years.
Therefore, Asha's present age is 27 years and Nisha's present age is 5 years.
How many solutions does this system have?
Answer:
x=0, exactly one solution.
Step-by-step explanation:
y=3x+3
y=-2x+3
-----------
3x+3=-2x+3
3x-(-2x)+3=3
3x+2x+3=3
5x+3=3
5x=3-3
5x=0
x=0/5
x=0
2x - 2(4x-3) = 6 - 6x
Answer:
x=
Step-by-step explanation:
Open parenthesis first:
2x-8x+6=6-6x
Combine like terms:
-6x+6=6-6x
Then move all like terms to one side:
6-6=-6x+6x
Simplify:
0=0
0=0 is true, so x can equal any number and the result will be true. (Like the number 4, for example. If x was 4, you would get 4=4.)
~Stay golden~ :)
a
The hypotenuse of a right triangle is 15 centimeters long. One leg is
9 centimeters long. How long is the other leg?
The other leg is 12cm long.
Step-by-step explanation:
Given,
Hypotenuse = c = 15cm
One leg = a = 9cm
Other leg = b
As the triangle is right angled, therefore, using Pythagoras theorem;
[tex]a^2+b^2=c^2\\(9)^2+b^2=(15)^2\\81+b^2=225\\b^2=225-81\\b^2=144\\[/tex]
Taking square root on both sides;
[tex]\sqrt{b^2} =\sqrt{144} \\b=12\ cm[/tex]
The other leg is 12cm long.
Keywords: triangle, square root
Learn more about triangles at:
brainly.com/question/5461619brainly.com/question/5510873#LearnwithBrainly
Find the distance between the points (7, 6) and (7, -4).
Answer:
If I'm correct it is 10.
Step-by-step explanation:
The distance was 10 ;-;.
Tip: use desmos for this
Beth read a total of 12 books over 7 months.
If Beth has read 84 books so far, how many months has she been with her book club?
Solve using unit rates.
She has been with her book club for 49 months.
Step-by-step explanation:
Books read = 12 books
Time period = 7 months
Therefore,
12 books = 7 months
1 book = [tex]\frac{7}{12}\ months[/tex]
Books read so far = 84 books
Total time period = x
84 books = x months
1 book = [tex]\frac{x}{84}\ months[/tex]
Using both unit rates;
[tex]\frac{x}{84}=\frac{7}{12}\\x=\frac{7}{12}*84\\x=\frac{588}{12}\\x=49\ months[/tex]
She has been with her book club for 49 months.
Keywords: Unit rates, multiplication
Learn more about multiplication at:
brainly.com/question/10699220brainly.com/question/10703930#LearnwithBrainly
Find values of a and b that make the following equality into identity:
Answer:
1. [tex]a=b=\dfrac{3}{4}[/tex]
2. [tex]a=-3,\ b=3[/tex]
Step-by-step explanation:
1. Given:
[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{a}{x-2}+\dfrac{b}{3x+2}[/tex]
To find a and b, add two fractions in right side:
[tex]\dfrac{a}{x-2}+\dfrac{b}{3x+2}\\ \\=\dfrac{a(3x+2)+b(x-2)}{(x-2)(3x+2)}\\ \\=\dfrac{3ax+2a+bx-2b}{(x-2)(3x+2)}\\ \\=\dfrac{(3a+b)x+(2a-2b)}{(x-2)(3x+2)}[/tex]
So,
[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{(3a+b)x+(2a-2b)}{(x-2)(3x+2)}[/tex]
Two fractions with same denominators are equal when they have equal numerators, so
[tex]3x=(3a+b)x+(2a-2b)[/tex]
Equate coefficients:
[tex]At\ x:\ \ 3=3a+b\\ \\At \ 1: 0=2a-2b[/tex]
From the second equation:
[tex]a=b[/tex]
Substitute it into the first equation:
[tex]3b+b=3\\ \\4b=3\\ \\b=\dfrac{3}{4}[/tex]
Hence,
[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{\frac{3}{4}}{x-2}+\dfrac{\frac{3}{4}}{3x+2}[/tex]
2. Given:
[tex]\dfrac{3}{x^2-5x+6}=\dfrac{a}{x-2}+\dfrac{b}{x-3}[/tex]
Note that [tex](x-2)(x-3)=x^2-3x-2x+6=x^2-5x+6[/tex]
To find a and b, add two fractions in right side:
[tex]\dfrac{a}{x-2}+\dfrac{b}{x-3}\\ \\=\dfrac{a(x-3)+b(x-2)}{(x-2)(x-3)}\\ \\=\dfrac{ax-3a+bx-2b}{(x-2)(x-3)}\\ \\=\dfrac{(a+b)x+(-3a-2b)}{(x-2)(x-3)}[/tex]
So,
[tex]\dfrac{3}{(x-2)(x-3)}=\dfrac{(a+b)x+(-3a-2b)}{(x-2)(x-3)}[/tex]
Two fractions with same denominators are equal when they have equal numerators, so
[tex]3=(a+b)x+(-3a-2b)[/tex]
Equate coefficients:
[tex]At\ x:\ \ 0=a+b\\ \\At \ 1: 3=-3a-2b[/tex]
From the first equation:
[tex]a=-b[/tex]
Substitute it into the second equation:
[tex]-3(-b)-2b=3\\ \\3b-2b=3\\ \\b=3\\ \\a=-3[/tex]
Hence,
[tex]\dfrac{3}{x^2-5x+6}=\dfrac{-3}{x-2}+\dfrac{3}{x-3}[/tex]
To turn an equality into an identity, you would find values for 'a' and 'b' that work for all values of 'x'. The process involves equating coefficients and solving the resulting equations. Without specific equations, we must rely on general methods, such as using the quadratic formula when 'c' is known.
Explanation:Finding Values of a and b
To make the equality into an identity, you'll typically want to find values of 'a' and 'b' that satisfy the given equations for all values of 'x'. It seems like part of your question is missing, as we would need the specific equations to give a precise answer. However, the process involves equating coefficients of the same powers of 'x' from both sides of the equation and solving the resulting system of equations.
For example, if you have an equation of the form ax2 + bx + c = 0 and you want to make it an identity, you can find 'a' and 'b' by applying the quadratic formula when 'c' is given.
In the case of a quadratic equation ax2 + bx + c = 0, you can determine 'a' and 'b' by solving:
-b ± √(b2 - 4ac) / (2a)
Which simplifies down when given specific constants, as shown by the example where a = 3, b = 13, and c = -10. This yields two possible solutions for 'x' which can verify the values of 'a' and 'b'.
If an equation already has set constants like a = 1.00, b = 10.0, and c = -200, then the equation is already defined, and the values are given.